(untitled) (Eurasian Medical Research Periodical, 2022)
In recent decades, traumatism has become one of the most pressing problems of modern medicine due to the ever-increasing number of injuries and the high mortality and disability of the injured. In recent years, traumatic deaths have been measured by the number of "non-lived years"; injury-related deaths exceed those caused by cardiovascular diseases, cancers and infectious diseases taken together. This is understandable as the vast majority of deaths from injuries are young people and children.